Modern Mormonism: myths and realities - Millet, Robert L. (Greg Kofford Books, 2011)
Robert L. Millet provides important clarifications for Latter-day Saints about eleven of the most frequent myths used to discredit the Church. He also models how to conduct such a Bible based discussion respectfully, illustrated with his personal experiences growing up in a non-Mormons community, speaking with others of different faiths, and working with his students at Brigham Young University